Appendicitis in pregnancy: how to manage and whether to deliver. (3rd April 2015) - Weston, Polly; Moroz, Paul
<x xml:space="preserve">Abstract</x> Key content Appendicitis in pregnancy is common. Whether to deliver a pregnant woman with appendicitis is a contentious issue. There are many uncertainties with diagnosis of appendicitis in pregnancy. Management of pregnant women with appendicitis requires a multidisciplinary approach involving obstetricians, anaesthetists and surgeons. Learning objectives To understand the modalities useful in accurate diagnosis of appendicitis in pregnancy. To learn about the range of clinical presentations and differential diagnoses. To appreciate the risks involved with different management options, anaesthetic and surgical. To be able to manage a pregnant woman with suspected appendicitis for the best possible outcome. Ethical issues Operative delivery of a pregnant woman with appendicitis may put her at unnecessary risk. How should she best be managed for the best possible outcome for her and the fetus?